Role of core body temperature in nephrolithiasis. (26th August 2020) - Srirangapatanam, Sudarshan; Wiener, Scott; Stoller, Marshall L.
Abstract : Objectives: To assess the role of core body temperature in urinary stone formation using a large clinical dataset. Patients and Methods: We retrospectively collected 14 519 039 individual temperature measurements from 580 416 patients with medical history, laboratory values and medication history between 2013 and 2018 at a single institution. After exclusions and matching 2:1 (controls:cases) to account for confounding variables, 7104 patients with a history of urinary stones were identified. Results: Patients with a history of urinary stones (cases) had an elevated mean (SD) oral temperature compared to matched controls, at 36.666 (0.17) vs 36.659 (0.20)°C ( P  = 0.012). Logistic regression of matched samples showed that higher core body temperature was predictive of a history of nephrolithiasis (odds ratio 1.21, 95% confidence interval 1.04–1.4; P  = 0.015). Conclusion: Core body temperature was significantly higher in patients with a history of urinary stones compared to matched controls, contrary to the anticipated thermodynamic considerations leading to crystal aggregation. Given that the core body temperature is elevated, rather than decreased, thermodynamic process driving stone formation is unlikely.